Mid-Turonian ammonite faunas from northern Mexico - Kennedy, W; Cobban, W (1988)
Turonian ammonite assemblages are described from six localities in the Ojinaga and Boquillas formations of Chihuahua in northern Mexico. These assemblages reveal the presence of the middle Turonian zones of Collignoniceras woollgari and Prionocyclus hyatti far to the south of previously documented occurrences. The Mexican collections include co-occurring collignoniceratids, known from as far north as Montana, and Tethyan euomphaloceratines and coilopoceratids. One species, Puzosia (Puzosia) serratocarinata, is new. -Authors